Robbing Peter to pay Paul: a welfare analysis of minimum wage under indexation - Mendes, Gustavo Mafra (2024)
The post-redemocratization period in Brazil saw a significant rise in public expenditures indexed to the National Consumer Price Index (INPC) and the minimum wage, reaching 9.96% of GDP by 2019. Specifically, expenses tied to the minimum wage surged from 1.48% to 5.23% of GDP between 1996 and 2019, driven by real wage increases. Concurrently, the informal labor market persisted at around 39.1% of the workforce, mirroring levels from 1996. Employing a quantitative model with heterogeneous agents and the presence of an informal sector, calibrated for 1996, this study analyzes the impact of government expenditure indexation on worker welfare, particularly for minimum wage earners. Results show that while minimum wage hikes generally boost welfare, it worsens the welfare of workers in the bottom of the distribution, while boosting the welfare of those at the top. The tax burden to finance indexed expenditures diminishes these gains, leaving workers with only 96.65% of the potential welfare increase without expenditure indexation, if adjustment is made via revenue taxes.